Produções de animações em stop motion na aula de física: possibilidades de novas percepções - Morais, Danilo de (Universidade Federal de São Carlos, 2021)
In this text I describe the application of the educational product carried out for the preparation of the dissertation of the MNPEF (National Professional Master's Degree in Physics Teaching). The developed product is a text material to guide the production of stop motion animations in the teaching of Physics. The work is based on the concept of perception proposed by Gestalt thinkers. One of the main representatives of Gestalt, Arnheim criticizes the exclusion of intuition in science education as opposed to an overvaluation of inductive logical reasoning. This work is inspired by this criticism to propose a method of visual creation that can be adopted by the teacher as an alternative for visual production that does not depend on computer programming skills typically used in making educational animations and simulators. The creation of stop motion can also be a tool for exercising intuition when produced by students. As for the application in the classroom, both possibilities were tested: video creation by the teacher using concepts of visual perception in the study of movements and the production of videos by students to exercise their perception and also to test the ease of execution of the procedures. guidance material.
Stop motion animations in physics classroom: possibilities for new perceptions
Keywords: Gestalt; Stop motion; Physics teaching; Ensino de Física; Animação; Animation; Movimento; Movement; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO